Low molecular weight EPS II of Rhizobium meliloti allows nodule invasion in Medicago sativa. - González, J E (1996)
Effective invasion of alfalfa by Rhizobium meliloti Rm1021 normally requires the presence of succinoglycan, an exopolysaccharide (EPS) produced by the bacterium. However, Rm1021 has the ability to produce a second EPS (EPS II) that can suppress the symbiotic defects of succinoglycan-deficient strains. EPS II is a polymer of modified glucose-(beta-1,3)-galactose subunits and is produced by Rm1021 derivatives carrying either an expR101 or mucR mutation. If the ability to synthesize succinoglycan is blocked genetically, expR101 derivatives of Rm1021 are nodulation-proficient, whereas mucR derivatives of Rm1021 are not. The difference in nodulation proficiency between these two classes of EPS II-producing strains is due to the specific production of a low molecular weight form of EPS II by expR101 strains. A low molecular weight EPS II fraction consisting of 15-20 EPS II disaccharide subunits efficiently allows nodule invasion by noninfective strains when present in amounts as low as 7 pmol per plant, suggesting that low molecular weight EPS II may act as a symbiotic signal during infection.